Một phương pháp nghiên cứu ngưỡng mưa nhằm cảnh báo trượt lở đất - An, Lê Đức (Vietnam Journal of Earth Sciences, 2012)
SUMMARYA method for study of rainfall thresholds for landslide warningTo follow the experience of U.S. and European scientists using the rainfall thresholds for landslide warning, in this paper the author attempts to establish the preliminary rainfall thresholds causing landslides in Ha Giang province, on the basis of field works (2006-2008), the reports about natural hazards of locality, and the rainfall data of the main rain gauges of Province during the periodof 2000-2008. Two rain phases of a storm evolution causing landslides were determined, as phase of preparation and phase of effect. The rains directly caused this disaster(in phase of effect) are often unusual big rainfalls. Rainfall thresholds were defined for Ha Giang Town, with : Pef = -0.335Ppr + 210.371 and Ief = -3.016 Ipr + 8.328. At the same time a alert line of landslides for location had been done on the basis of P-D chart compiling.